Bullying dan Mental Hygiene Santri di Pondok Pesantren Jember - ., Wahyuni; Ernawati, Sitti (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
This study reviews the impact of bullying and mental hygiene of students at Islamic boarding schools in Jember which often occurs in the world of non-formal education such as Islamic boarding schools. This study aims to describe how bullying occurs and the impact experienced because of bullying and how to prevent bullying behavior. This type of research is qualitative research, while the research instruments are observation, interview guides, and researchers key instruments. The data source for this research is the results of interviews with school principals, ustadz and ustadzah, and administrators of Islamic boarding schools. The result is to provide an understanding of the negative impact of bullying behavior on the mental hygiene of students or students both at school and in Islamic boarding schools. To minimize bullying behavior in the future.